2008
DOI: 10.1038/sj.bdj.2008.300
|View full text |Cite
|
Sign up to set email alerts
|

A practical skill one day medical emergencies course for dentists and DCPs

Abstract: This paper describes a practical skills one day course in the 'management of medical emergencies' which is aimed at fulfilling the requirements for training for dentists and DCPs as defined by the Resuscitation Council UK and prefaced by the GDC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 1 publication
0
13
1
Order By: Relevance
“…Students also felt strongly that this training should be incorporated into undergraduate teaching (4.86 ± 0.35). These results reiterate the findings of Balmer et al 21 which found simulation training, tailored for dentists' needs, to be highly effective.…”
Section: Discussioncontrasting
confidence: 47%
“…Students also felt strongly that this training should be incorporated into undergraduate teaching (4.86 ± 0.35). These results reiterate the findings of Balmer et al 21 which found simulation training, tailored for dentists' needs, to be highly effective.…”
Section: Discussioncontrasting
confidence: 47%
“… 26 For many years the simulation training has been done successfully for medical students; therefore, it seems that this method should be used for dental students in order to training medical emergencies. 27 28 …”
Section: Discussionmentioning
confidence: 99%
“…21,22 There is also subjective evidence that simulation-based learning is valued highly by medical students. 17,23,24 Simulation and role-play techniques offer unique opportunities to maximize familiar-ization with a scenario in a safe and guided environment. 17 This provides repetition, allowing development of psychomotor skill, followed by practice with continual re-enforcement to encourage confidence in skills -an essential element to developing confidence and competence in managing medical emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…17 This provides repetition, allowing development of psychomotor skill, followed by practice with continual re-enforcement to encourage confidence in skills -an essential element to developing confidence and competence in managing medical emergencies. 17,23 Benefits of simulation-based techniques in this programme were further augmented by using a 'pause and discuss' approach allowing students to perform each skill, clarify knowledge, receive immediate corrective feedback and encouragement or further instruction. 12 This method exposes students to a realistic scenario, but allows for 'freezing' of the simulation to enable facilitator support.…”
Section: Discussionmentioning
confidence: 99%